2014
DOI: 10.1149/2.0561503jes
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up Filling of through Silicon Vias Using Galvanostatic Cu Electrodeposition with the Modified Organic Additives

Abstract: The chemically synthesized suppressor and leveler are added together with bis(3-sulfopropyl)disulfide (SPS) to galvanostatically fill up the trenches with the similar dimensions to those of the through silicon vias. In our previous study, the deposition of the coarse-grained Cu was indicated as a drawback of the synthesized additives, i.e., polyoxy polymer with amine terminal groups and pyridine derivatives containing additional amine groups. In this study, the modified chemistry of organic additives is used, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…[25][26][27] This combination of organic additives was quite similar to the aforementioned V-shape filling. However, selective accumulation of the accelerator at the bottom of the features was additionally applied to TSV filling.…”
supporting
confidence: 62%
“…[25][26][27] This combination of organic additives was quite similar to the aforementioned V-shape filling. However, selective accumulation of the accelerator at the bottom of the features was additionally applied to TSV filling.…”
supporting
confidence: 62%
“…[18][19][20][21][22][23] Replacing traditionally used acid-based electrolytes with weak organic acid based electrolytes has recently been studied for copper deposition in through-holes on printed circuit boards. 24,25 These studies showed that replacement of H 2 SO 4 with acetic acid improved film quality.…”
mentioning
confidence: 99%
“…Owing to the merits of high throughput, low process cost, and good film quality, Cu electroplating has a wide application, from traditional Cu foil production to state-of-the-art semiconductor metallization processes. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The Cu plating solution typically contains small amounts of organic additives, 1-16 which enhance the uniformity, 13 brightness, 14 and mechanical properties of the Cu film. 15 In addition, for particular application to damascene Cu plating, the additives enable bottom-up filling at trenches or vias by controlling the relative deposition rates of Cu at the top and bottom of the features.…”
mentioning
confidence: 99%